Analisis Persepsi Akuntansi Terhadap Implementasi Standar Akuntansi Keuangan di Perusahaan Konveksi - Nisa Amalia (Ikatan Da'i Indonesia, 2025)
This research is to investigate, using a case study at Wakid Konveksi, the accounting view of the application of Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM) in a convection firm. This research explores in-depth the experiences and knowledge of business actors on the application of accounting standards by means of a qualitative methodology including observation techniques, in-depth interviews, and documentation studies. The research included owners and financial staff members directly involved in the financial reporting process. The findings of the research show that while management understands the need of using SAK EMKM in improving transparency and the quality of financial reporting, the implementation has not been most ideal. The primary challenges discovered include poor knowledge of SAK, few accounting experts, and little help and training. Given the situation of microbusiness, certain elements of SAK are also seen as overly complex and challenging to use. Other results show that, with enough training, digital technology might be a solution helping SAK to be implemented. This research underlines how much the effectiveness of using SAK depends on the opinions of internal preparedness, business players, and sufficient outside support.